Prediction of spatially distributed seismic demands in specific structures structural response to loss estimation. - Bradley, Brendon A. (Earthquake engineering & structural dynamics.)
A companion paper has investigated the effects of intensity measure (IM) selection in the prediction of spatially distributed response in a multi-degree-of-freedom structure. This paper extends from structural response prediction to performance assessment metrics such as probability of structural collapse; probability of exceeding a specified level of demand or direct repair cost; and the distribution of direct repair loss for a given level of ground motion. In addition, a method is proposed to account for the effect of varying seismological properties of ground motions on seismic demand that does not require different ground motion records to be used for each intensity level. Results illustrate that the conventional IM, spectral displacement at the first mode, Sde (T1), produces higher risk estimates than alternative velocity-based IM's, namely spectrum intensity, SI, and peak ground velocity, PGV, because of its high uncertainty in ground motion prediction and poor efficiency in predicting peak acceleration demands.